Koncokelas: Aplikasi Video Pembelajaran Berbasis Animasi sebagai Usaha Pemberdayaan Anak Putus Sekolah melalui Rumah Belajar - Yorizal Tri M Gulo; Ahmad Kevin Nasution; Beby Masitho Batubara; Servista Waruwu (Pelita Masyarakat, 2021)
The service activities in Duria Village aim to improve the quality of individuals in the context of human resource development, form community cadres as agents of change, become a pillar of pride for the community and know the work process and how to implement community empowerment activities with Concloc activities. The implementation of activities is carried out using 4 (four) stages, namely: the initial stage of introducing and planting material, values and norms to school dropouts in Duria Village, the second stage is to develop the orientation of Koncokelas cadres, the third stage is a continuation of the stage the first and second stage, and the last stage, where at this stage the Koncokelas Cadres are ready to carry out field activities. The service that was carried out in Duria Village was carried out for 4 (four months). In this service activity, the target audience is school dropouts aged 10-15 years. The concept of service, namely Koncokelas: Application of Animation-Based Learning Videos as Efforts to Empower School Dropouts through Learning Houses. The result of this dedication is that the Classroom activities have succeeded in increasing the knowledge and skills of school dropouts as well as increasing their interest and motivation to learn.